2018
DOI: 10.1111/hiv.12636
|View full text |Cite
|
Sign up to set email alerts
|

Similar long‐term efficacy of dual therapy containing raltegravir and a boosted protease inhibitor versus standard triple therapies in pretreated HIV‐1‐infected patients in a retrospective, real‐life cohort of 14 years

Abstract: These data indicate that, in a real-life setting, raltegravir can be used with a high virological success rate in treatment-experienced patients, and that the different combinations analysed (2NRTIs + RAL, bPI + RAL and others) show comparable rates of virological suppression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…In the SPARE study, there was no significant difference between DRV/r plus raltegravir and lopinavir/ritonavir plus tenofovir/emtricitabine [9]. Several observational studies further assessed this combination and demonstrated viral success in 75.5% to 97.6% of patients [10][11][12]. The use of raltegravir, a drug with relatively low genetic barrier and twicedaily administration at that time, could have affected the overall results, as described in other studies [9].…”
Section: Discussionmentioning
confidence: 98%
“…In the SPARE study, there was no significant difference between DRV/r plus raltegravir and lopinavir/ritonavir plus tenofovir/emtricitabine [9]. Several observational studies further assessed this combination and demonstrated viral success in 75.5% to 97.6% of patients [10][11][12]. The use of raltegravir, a drug with relatively low genetic barrier and twicedaily administration at that time, could have affected the overall results, as described in other studies [9].…”
Section: Discussionmentioning
confidence: 98%
“…The requirement for lifelong antiretroviral therapy (ART) to maintain viral suppression in people living with HIV (PLWH) has increased the interest in developing effective dual therapy (DT) regimens to reduce cumulative drug exposure and cost, and to simplify regimens 1,2 . Several studies have demonstrated that when compared with triple therapy (TT), DT has non‐inferior virological responses and CD4 cell recoveries when used as a switch strategy in virologically suppressed, ART‐experienced patients 3‐5 . Randomized clinical trials have demonstrated similar results in ART‐naïve patients starting treatment, when comparing DT regimens based on boosted protease inhibitors (PIs) and integrase strand transfer inhibitors (INSTIs) with similar TT regimens 6–8 .…”
Section: Introductionmentioning
confidence: 99%